IPI Removing by Using Reference Sign/N-ary Orthogonal Coded/Balanced TR-UWB Receiver for WPAN Based on Hadamard Matrix - Al-Qaraawy, Saleh M. (Nahrain University College of Engineering Journal, 2009)
IR UWB system has been proposed as a promising physical layer candidate for indoor wireless communications, because it offers very fine time resolution and multipath resolvability. Inter pulse interference (IPI) is one important challenge related to the transmit reference (TR) IR UWB receiver. In this paper, an attempt to completely remove the IPI problem in TR with increasing the data rate. This is achieved by using orthogonal codes generated from modified version of Hadamard matrix via the application of the reference sign technique, i.e., by modulating the reference pulse besides the already data modulated